The classical and modern sociology of knowledge: paradigm approach - N. V. Nikolina; A. E. Strelyaeva (Омский научный вестник: Серия "Общество. История. Современность")
There are discusses the classical and modern sociology of knowledge from the position of a paradigm approach in this article. The basis of the classical paradigm of the sociology of knowledge is the theory of social knowledge and the actions of K. Marx, M. Weber, E. Durkheim and K. Mannheim. The inclusion of science as a material for sociological analysis led to the formation of the modern paradigm of the sociology of knowledge, whose representatives are D. Blur, S. Barnes, B. Latour and S. Woolgar